Does relational capital matter to food and beverage SMEs’ resilience? The mediating role of environmental scanning - YahiaMarzouk, Yasmine; Jin, Jiafei (Frontiers in Psychology, 2022)
The COVID-19 pandemic’s characteristics, including how quickly it spread, and the emergence of new virus variations, raise serious questions about the pandemic’s potential repercussions and complications in the food and beverage industry, among other industries. The global COVID-19 pandemic highlights the pressing need to reconsider how we manufacture and market food and beverage goods. During the epidemic, SMEs must build organizational resilience (OR) in order to recover economically, socially, and communally. Relational capital (RC) is a crucial factor that can be deployed by SMEs to acquire the resources existing in the external networks to adapt to disturbances; however, the impact of RC on the resilience of Egyptian food and beverage SMEs is under-examined. Additionally, it is unclear how RC promotes organizational resilience. In this regard, we argue that social interactions and regular communication can let an SME and its business partners exchange information and best practices, thereby enabling it to immediately establish backup plans to deal with the disruption. In order to achieve our aim, we investigated how relational capital affected organizational resilience both directly and indirectly through environmental scanning, utilizing partial least squares structural equation modeling (PLS–SEM).The results from 217 Egyptian food and beverage SMEs demonstrate that relational capital directly and positively affected organizational resilience. Besides, the RC–OR relationship is partially mediated by environmental scanning. Our current study, therefore, adds to the extant literature through being one of the few studies to address the topics of relational capital and resilience altogether during crisis times within a developing country, an issue that has not been sufficiently investigated in exiting literature. Moreover, our current study is the first one to empirically investigate the role of relational capital in facilitating environmental scanning activities of SMEs to ultimately foster their resilience. Our results, thus, prove that a large amount of information relevant for recovery are inherent within an SME’s external relations network. We provide implications for theory and practice.